PENGEMBANGAN LEMBAR KERJA SISWA BAHASA INGGRIS BERMUATAN NILAI PENDIDIKAN KARAKTER KELAS V MADRASAH IBTIDAIYAH SEMARANG (Universitas Negeri Semarang, 2013)
AbstrakTujuan penelitian ini adalah mendeskripsikan kebutuhan terhadap LKS, meru- muskan prinsip penyusunan LKS, mengukur kevalidan LKS dan membuktikan keefektifan LKS bahasa Inggris bermuatan nilai karakter kelas V MI. Penelitian pengembangan ini mengikuti model Borg and Gall. Data penelitian diperoleh mela- lui pemberian angket, lembar penilaian, dan tes. Teknik analisisdata menggunakan t-tes dan N-gain. Hasil penelitian ini adalah 1) pemenuhan kebutuhan LKS meliputi aspek desain, isi dan ranah karakter; 2) prinsip penyusunan LKS meliputi prinsip kebermaknaan, keterpaduan dan estetika; 3) kevalidan LKS termasuk dalam kat- egori sangat baik; dan 4) LKS bahasa Inggris bermuatan nilai pendidikan karak- ter sangat efektif dalam meningkatkan hasil belajar siswa berdasarkan hasil perhi- tungan t test dan N-gain. Produk LKS bahasa Inggris bermuatan nilai pendidikan karakter perlu diujicobakan dalam skala luas. AbstractThe purposes of this research are describing needs to English student worksheet, formulating the principles of English student worksheet’s arrangement, measuring the validity of English student worksheet and going to show the effectiveness of English student worksheet consisting character education values of fifth grade students of Islamic elementary school. This rese- arch and development refers to Borg dan Gall’s model. The data collecting techniques uses students and teachers’ need questionnaire, expert assessment and test, then it is analyzed by t-test statistic and normalized gain. The result of this research are 1) fulfillment of English students worksheet’s need, include design, content and character domain; 2) the principles of English students worksheet’s arrangement include meaningfull, cohesiveness and aesthetics; 3) the validity of English student worksheet includes the excellent category; and 4) English student worksheet consisting character education values is very effective in increasing the stu- dent learning outcomes based on the calculation of t-tes and normalized gain. English student worksheet’s product consisting character education values needs to be tested in a wide scale.